Find the sum of all possible positive integers that
is a perfect square.
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
If the above equation is to equal a perfect square, then let us write:
2^(2n-1) - 2^n + 1 = a^2;
or 2*2^(2n-2) - 2^n + 1 = a^2;
or 2 2^(2n-2) - 2 2^(n-1) + 1 = a^2;
or 2^2(n-1) + 2^2(n-1) - 2*2^(n-1) + 1 = a^2;
or [2^(n-1)]^2 - 2*2^(n-1) + 1 = a^2 - [2^(n-1)]^2;
or [2^(n-1) - 1]^2 = [a + 2^(n-1)][a - 2^(n-1)].
Now, let us now equate the terms:
a - 2^(n-1) = 1 (i); a + 2^(n-1) = [2^(n-1) - 1]^2 (ii).
whereby solving (i) for 2^(n-1) in terms of a yields: a-1 = 2^(n-1), and substituting this value into (ii) produces:
a + (a-1) = [(a-1) - 1]^2 => 2a - 1 = (a - 2)^2 => 2a - 1 = a^2 - 4a + 4 => 0 = a^2 - 6a + 5 => 0 = (a-1)(a-5) => a = 1 or 5.
A quick check in (i) produces a = 1 => 2^(n-1) = 0 and a = 5 => 2^(n-1) = 4, which only the second choice is valid and ultimately yields n = 3. Next, let us examine the form:
2^(2n-1) - 2^n = a^2 - 1;
or (2^n)*[2^(n-1) - 1] = (a+1)(a-1)
and equate the larger and the smaller term respectively as:
2^n = a + 1 (iii) 2^(n-1) - 1 = a - 1 (iv)
or 2^n = 2a after simplifying (iv). Substituting this expression into (iii) ultimately produces: 2a = a + 1 => a = 1 and finally n = 1.
Thus, the only values of n that can ever produce a perfect square of the form 2^(2n-1) - 2^n + 1 are n = 1, 3 which sum to 4.